2010
DOI: 10.1007/s11581-010-0434-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of methyl methacrylate graft-copolymerized composite separator based on radiation polymerization technique

Abstract: The pre-irradiation method is introduced to prepare methyl methacrylate graft-copolymerized composite separators. The morphologies of the grafted membranes (GMs) were observed under a scanning electron microscope. The cyclic voltammetry and electrochemical impedance spectra results indicated that the obtained polymer electrolytes (PEs) based on GMs could hold the excellent performance of Li + transportation and possess good affinity with Li metal electrode. The Li/PEs/LiCoO 2 cells demonstrated excellent cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…[9][10][11][12][13] Oftentimes, radiation treatment (plasma, corona discharge, electron beam, g-ray, UV, photons) is applied to activate the polyolefin surface and to facilitate subsequent functionalization. [9][10][11][12][13][14] Alternatively, incorporation of inorganic nanoparticles including SiO 2 , TiO 2 , Al 2 O 3 , MgO, g-LiAlO 2 , and CaCO 3 into various polymers is also a well-studied route to improve the performance of battery separators. [16][17][18][19][20] The nanoparticles can be either dispersed in the polymer matrix to form a composite membrane, or can be initially combined with a suitable binder material and then deposited on a nonwoven support.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12][13] Oftentimes, radiation treatment (plasma, corona discharge, electron beam, g-ray, UV, photons) is applied to activate the polyolefin surface and to facilitate subsequent functionalization. [9][10][11][12][13][14] Alternatively, incorporation of inorganic nanoparticles including SiO 2 , TiO 2 , Al 2 O 3 , MgO, g-LiAlO 2 , and CaCO 3 into various polymers is also a well-studied route to improve the performance of battery separators. [16][17][18][19][20] The nanoparticles can be either dispersed in the polymer matrix to form a composite membrane, or can be initially combined with a suitable binder material and then deposited on a nonwoven support.…”
mentioning
confidence: 99%
“…Modifications of the polyolefin surface can improve the wetting characteristics of the separators but the chemistry is rather challenging and the performance depends critically on the nature and the grafting density of the functional groups. [8][9][10][11][12][13][14][15] To that end, graft polymerization of methylmethacrylate, glycidyl methacrylate, acrylic acid onto polyolefin separators has been described. [9][10][11][12][13] Oftentimes, radiation treatment (plasma, corona discharge, electron beam, g-ray, UV, photons) is applied to activate the polyolefin surface and to facilitate subsequent functionalization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that resultant separators exhibited improved thermal (lower M a n u s c r i p t 49 thermal shrinkage) and electrochemical properties (higher oxidation stability), higher electrolyte uptake and ionic conductivity compared the unmodified commercial PE separators [235]. Gao et al [228] described the synthesis and characterization of composite separators by radiation-induced grafting in detail. Pre-irradiation of the commercial three layer (PP/PE/PP) micro-porous separator by γ-rays, followed by grafting with MMA and finally activation by immersion in liquid electrolyte to obtain membranes with the desired properties.…”
Section: Lithium Batteriesmentioning
confidence: 99%
“…A schematic of the processing of Li-ion polymer battery membranes based on pre-irradiation graft copolymerization technique is shown in Figure 27 [228].. The resultant polymer electrolytes exhibited high ionic conductivity, superior electrochemical stability up to 4.6 V, combined with very promising cycling performance and reversibility of lithium ions.…”
Section: Lithium Batteriesmentioning
confidence: 99%